2002
DOI: 10.1097/00005344-200209000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Phytoestrogens and Their Synthetic Structural Analogues as Calcium Channel Blockers in Human Platelets

Abstract: Phytoestrogens have been shown to inhibit platelet activation by blocking platelet calcium channels. This study examined the effect of several synthetic derivatives of trans-resveratrol, genistein, and daidzein on platelet free intracellular calcium ([Ca2+]i) elevation in thrombin-activated platelets and the possible mechanisms of this inhibitory effect. Studies were conducted on fresh human platelets from healthy volunteers. The fluorescent dye fura-2 was used to monitor [Ca2+]i in platelets. At 10 microM-res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…2: A and C) may support this view. Dobrydneva et al (11) reported that daidzein and other phytoestorgens block calcium influx in human platelets at 10 m M. The block of the nicotinic receptor reported here and that of calcium influx (11) are nongenomic actions because they are acute effects and insensitive to antiestrogen. As for genomic actions, the estrogen-mimetic activity of isoflavonoid phytoestrogen has been reported to be 3 or 4 orders less potent than that of 17b-estradiol (1).…”
mentioning
confidence: 50%
“…2: A and C) may support this view. Dobrydneva et al (11) reported that daidzein and other phytoestorgens block calcium influx in human platelets at 10 m M. The block of the nicotinic receptor reported here and that of calcium influx (11) are nongenomic actions because they are acute effects and insensitive to antiestrogen. As for genomic actions, the estrogen-mimetic activity of isoflavonoid phytoestrogen has been reported to be 3 or 4 orders less potent than that of 17b-estradiol (1).…”
mentioning
confidence: 50%
“…It is a weak ER agonist/antagonist with equal binding activity for ERα and ERβ (24), but the relative extent of its in vivo estrogencity is cell type-dependent (67). Other activities of resveratrol consistent with phytoestrogenic properties and positive effects on cardiovascular health include enhancement of expression and activity of endothelial nitric oxide synthase (187), inhibition of platelet activation (49), and suppression of oxidative DNA damage (139). However, a study concluded that resveratrol is inactive in immature rat uterotrophic assays and questioned the degree of ER binding by resveratrol and its significance for the compound's cardiovascular activity (14).…”
Section: Potential Health Beneficial Effectsmentioning
confidence: 99%
“…Since in vitro experiments demonstrated inhibition of platelet function and of endothelial tissue factors by RSV (74), it is conceivable that RSV may decrease blood coagulation and thrombus formation. The recently reviewed (26,87) in vitro inhibition of platelet aggregation in response to various agonists (thrombin, ADP and collagen) has been linked to the inhibition of eicosanoid synthesis (76) and to platelet calcium channels (20). However, it is more likely that RSV interferes with some of the other factors involved in hemostasis and thrombosis, rather than platelet aggregation.…”
Section: Inhibition Of Ldl Oxidationmentioning
confidence: 99%